Predictors of bone fractures in a single-centre cohort of hemodialysis patients: a 2-year follow-up study - Brunerová, Ludmila; Lažanská, Renata; Kasalický, Petr; Verešová, Jana; Potočková, Jana; Fialová, Alena; Rychlík, Ivan (International urology and nephrology, 2018)
PURPOSE: Bone involvement represents one of the complications of end-stage chronic kidney disease, with fractures being its major risk. The aim of our study was to assess the frequency and predictors of low-trauma fractures in a cohort of maintenance hemodialysis patients followed-up on for 2 years. METHODS: 59 patients (67.6 ± 13.1 years, 43 males) treated with hemodiafiltration underwent initially laboratory (markers of calcium-phosphate metabolism and bone turnover markers) and densitometry examination with TBS assessment (Lunar Prodigy, TBS software 2.1.2). During 24-month follow-up, the frequency of low-trauma fractures was assessed and possible predictors of increased fracture risk were identified using product-moment correlation matrices. RESULTS: Altogether 7 (11.9%) low-trauma fractures were observed. In the whole group, age (P = 0.047), T-score in proximal femur (P = 0.04), low vitamin D, low BMI (P = 0.03 for both), and higher FRAX for major osteoporotic fracture (P = 0.01) were connected with fractures, but in multi-variate analysis only BMI remained significantly negatively associated with fractures (P = 0.047). TBS and bone turnover markers failed to predict fractures. However, women with fractures had significantly lower serum phosphate (P = 0.03) and higher parathyroid hormone (P = 0.04). Parameters of hip structure analysis significantly correlated with FRAX, but not with fractures. CONCLUSIONS: In a group of hemodialysis patients from one centre, T-score in proximal femur, low vitamin D, low BMI, and high FRAX for major osteoporotic fracture were associated with low-trauma fractures, however, in multi-variate analysis only low BMI remained a significant predictor of fracture risk.
Keywords: Male; Risk Factors; Kidney Failure, Chronic; chronické selhání ledvin; následné studie; parathormon; acyltransferasy; Parathyroid Hormone; Aged; mužské pohlaví; senioři; vitamin D; Follow-Up Studies; hemodiafiltrace; senioři nad 80 let; proteiny z Escherichia coli; Acyltransferases; lidé; ženské pohlaví; Escherichia coli Proteins; Humans; kostní denzita; Body Mass Index; rizikové faktory; Aged, 80 and over; Bone Density; index tělesné hmotnosti; Vitamin D; Female; fraktury kostí; Hemodiafiltration; lidé středního věku; Fractures, Bone; Middle Aged